The Redefinition and Co-Production of Public Services by Urban Movements. The Can Batlló Social Innovation in Barcelona - Asara, Viviana (PARTECIPAZIONE E CONFLITTO, 2019)
A wealth of social innovations sprang up in recent years in Southern Europe in the bosom of urban movements to cover citizens´ needs from below. Reacting to the commodification of the neoliberal city and the increasing dismantling of the welfare state, they provide public services and interrelate in var-ious forms with state authorities. Drawing on the outstanding social innovation case of Can Batlló (CB) in the city of Barcelona, a 14-ha former factory including more than 30 different projects and involving more than 350 activists, this paper analyses how social movements are redefining "the public" in the articulation between institutionalization, public service co-production, disruptive repertoires of action, and autonomy. It argues that this multiplicity of strategies and the strength of the movement helped not only to avoid turning the CB social innovation into a neoliberal rollout strategy, but even to act as a safety cordon against austerity politics. Affecting the boundaries of the legal-institutional framework, and rejecting the conflation of "public goods" with "state goods", CB organizes public services provision and planning in a more democratic form, pressuring the government to deliver the promised public services, while reclaim-ing them as commons that activists contribute building and designing. CB´s movement dimension and rootedness in the neighbourhood ensure the prioritisation of public and neighbourhood concerns over short-term, particularistic, and organizational survival interests.